2020
DOI: 10.1590/s1677-5538.ibju.2019.0515
|View full text |Cite
|
Sign up to set email alerts
|

Kidney displaced by giant retroperitoneal liposarcoma in HIV patient

Abstract: A 56-year-old male with a history of infection of human immunodeficiency virus over ten years, was referred to our center because of intermittent epigastralgia and gradual increase of abdominal girth in the last two months. Physical examination revealed palpable abdominal mass at the right upper quadrant measuring around 20cm. Laboratory examinations of complete blood counts, urine tests, and tumor markers were otherwise normal. CT scan of the abdomen showed a huge fatty mass of 23.3 x 22.9 x 34.5cm with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A RLS tumor that encases the kidney is a relative indication for nephrectomy. In this case, kidney conservation may be attempted but there is always a risk of incomplete resection [11,12] . Some authors reported an en-bloc resection of the RLS with kidney and showed that there was no histologic tumoral involvement of the kidney [13,14] as was the case of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…A RLS tumor that encases the kidney is a relative indication for nephrectomy. In this case, kidney conservation may be attempted but there is always a risk of incomplete resection [11,12] . Some authors reported an en-bloc resection of the RLS with kidney and showed that there was no histologic tumoral involvement of the kidney [13,14] as was the case of our patient.…”
Section: Discussionmentioning
confidence: 99%